Ways to promote fair trade practice in South Korea - Yang, Jin A (KDI School, 2011)
Fair Trade is defined by FINE (FLO, IFAT, NEWS!, EFTA)as a trading partnership based on dialogue, transparency, and respect that seeks greater equity in international trade. Essentially, it is an alternative approach to free trade. Recently, the Fair Trade movement has been gaining momentum in South Korea. The purpose of this thesis is to discuss the importance of Fair Trade practices and how they can be further promoted within South Korea. This discussion will focus especially on the history of the Fair Trade movement in the United Kingdom (hereafter UK), which has been a leader in its development. Using both historical and analytical approaches, I will examine various factors that have contributed to the success of this movement in the UK, especially the leadership role of the Fairtrade Foundation and the foundation’s promotion of ‘Fairtrade Towns.’ I will suggest that the system of Fairtrade Towns in the UK, essentially a Fairtrade certification body that officially recognizes areas for their commitment to the promotion of fair trade-certified goods, should be adopted as a strategy to advance the Fair Trade movement in South Korea. As of 2011, over 1,000 towns in 22 countries have been designated as Fairtrade Towns, and thousands of additional communities are currently working toward this designation. By comparing the Fair Trade movement in the UK and South Korea, this paper will clarify the potential benefits of introducing a similar Fairtrade Town initiative in South Korea. Although it is probably not feasible to begin a Fairtrade Town initiative in Korea immediately, this research will suggest ways of laying the groundwork through activities at the community and local government levels.
Thesis(Master) --KDI School:Master of Public Policy,2011
Keywords: United Kingdom.